(untitled) (Research, Society and Development, 2022)
The generation of free radicals is a physiological event resulting mainly from the cellular respiration process and the overactivation of the NOX leads to an excess production of ROS that is associated with oxidative stress. Chrysobalanus icaco, a medicinal plant that belongs to the Chrysobalanaceae family, possesses a high number of polyphenols, including phenolic acids and flavonoids. Due to its phytochemical composition, this study aimed to evaluate the antioxidant potential of the hydroalcoholic extract from the leaves of Chrysobalanus icaco (HECi) and the inhibitory potential of its main flavonoids against NOX. The in silico predictions of absorption, distribution, metabolism, excretion, and toxicity (ADMET), drug-likeness properties, and molecular docking with the enzyme NOX (PDB code 2CDU) were also performed to support the experimental results. The phytochemical screening of the HECi showed the presence of phenols and flavonoids. HECi performed an excellent antioxidant activity (IC50 = 8.1 μg/mL), probably due to its rich phenolic (220.11 ± 0.4 mg GAE/g) and flavonoid (110.98 ± 0.37 mg QE/g) constitution. The ADMET prediction indicated that myricetin and quercetin had the best pharmacokinetic parameters. The molecular docking results showed that myricetin and especially quercetin had strong docking score on NOX (ΔG = –8.1 kcal/mol and ΔG = –8.3 kcal/mol, respectively). Frontier Orbital’s analyzes (HOMO and LUMO) suggested that quercetin has better antioxidant properties than myricetin. Our results demonstrate for the first time the in silico action of quercetin against NOX, as well as reiterate the antioxidant potential of C. icaco.